1994
DOI: 10.1093/oxfordjournals.qjmed.a068890
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric outcome in alcoholic liver transplant patients

Abstract: We investigated drinking behaviour and psychiatric outcome of patients with alcoholic liver disease after liver transplantation, to help assess the advisability of the procedure in these patients. English-speaking patients (n = 20) transplanted for alcoholic liver disease and informants, and patients transplanted for non-alcoholic liver disease (n = 54), were assessed by semi-structured interviews and standardized questionnaires 1-6 years following transplantation. All alcoholics were abstinent for several mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
3
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 0 publications
0
58
3
2
Order By: Relevance
“…9,[11][12][13][14][15][16] These patients may return to a pattern of alcohol consumption that poten-tially damages the transplanted liver, as well as affects compliance with the immunosuppressive regimen and follow-up appointments, which may put the graft at risk. 2,17 Reported rates of recidivism vary between 0% and 95% 1,3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21] ; in part, this discrepancy can be attributed to the definition of recidivism used. There is a relatively low incidence of recidivism in short-term periods of follow-up [9][10][11] ; however, more recent studies suggested that recidivism rates increase with longer followup.…”
mentioning
confidence: 99%
“…9,[11][12][13][14][15][16] These patients may return to a pattern of alcohol consumption that poten-tially damages the transplanted liver, as well as affects compliance with the immunosuppressive regimen and follow-up appointments, which may put the graft at risk. 2,17 Reported rates of recidivism vary between 0% and 95% 1,3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21] ; in part, this discrepancy can be attributed to the definition of recidivism used. There is a relatively low incidence of recidivism in short-term periods of follow-up [9][10][11] ; however, more recent studies suggested that recidivism rates increase with longer followup.…”
mentioning
confidence: 99%
“…Short-term follow-up studies have documented a risk for recidivism after OLT in 7% to 95% of patients with a diagnosis of alcohol dependence or abuse. 5,6,[8][9][10][11][12][13][14][15][16][19][20][21][22] Alcohol-induced liver disease with resulting graft failure has been documented in liver transplant recipients. 2,3 An increasing number of patients die awaiting OLT because of a continual increase in the number of patients on the waiting list and minimal increases in donor supply in recent years (United Network for Organ Sharing, 1995).…”
mentioning
confidence: 99%
“…18 Prevalence of alcohol relapse after liver transplantation varies widely. [19][20][21] This wide range of relapse after liver transplantation reflects several methodological differences among studies, variable follow-up, and difference in definition of relapse (any alcohol intake versus harmful drinking). 21 Mackie et al 22 compared alcohol intake in alcoholics with other etiologies of liver transplantation and found similar rates.…”
Section: Predictors Of Relapsementioning
confidence: 99%